Knowledge and Attitudes Workers Toward Compliance Use Personal Protective Equipment - Noviarmi, Fadilatus Sukma Ika; Prananya, Lanobyan Hamengku (Universitas Airlangga, 2023)
Introduction: All chemical industries in Indonesia have a potential hazards that can cause work accidents, occupational diseases, and work-related diseases. In this case, one of the protective measures that can be carried out on occupational health and safety in the PA Plant area as a chemical industry is the obligation to use PPE for the workers. Related to this matter, current project was done to assess how workers' compliance to the usage of Personal Protective Equipment (PPE) related to knowledge, attitudes, and individual characteristics (age and educational attainment). Methods: The methodology applied to this study was analytical observational using a cross-sectional approach, where 37 workers were involved as research samples. In addition, a questionnaire and a compliance checklist for the usage of PPE were used to gather the data, and Spearman's Rho test was used to evaluate it. Results: The findings indicate that most employees are in the early adulthood group, graduated from a secondary school level, have excellent attitudes toward using personal protective equipment, have good understanding, and have good compliance with the use of PPE. It was further revealed that the PPE usage compliance does not in accordance with a person's age or level of knowledge. However, there is a relationship between knowledge and attitudes and compliance with the usage of PPE. Conclusion: Based on the findings discovered, it is summed up that although a good level of knowledge and attitude toward the use of PPE will make employees comply with the use of PPE, a worker's degree of education does not ensure their level of compliance with the use of PPE.